Mitigation of Disagreement in Peer Review among L2 Learners and Native Speakers in a College Writing Class - O'Donnell Christoffersen, Katherine (GIST – Education and Learning Research Journal, 2015)
Peer review is now a commonplace practice in process-oriented writing instruction. A crucial aspect of peer review is assessing another classmate’s work, which encompasses the act of disagreement. Given its prevalence in the classroom, it is necessary to analyze how L2 learners mitigate disagreement in the context of peer review with other L2 learners and native speakers. The present paper presents a qualitative analysis of action research from an introductory English writing class at the university level including native speakers of English and international students from different linguistic and cultural backgrounds. The conversation-based peer review sessions were analyzed for various mitigation strategies including token agreement, hedging, prefacing positive remarks and requests for clarification. The analysis shows that L2 learners and native speakers of English use similar mitigation strategies, and it demonstrates the coconstruction of meaning in peer review interactions.